On the aesthetic significance of imprecision in computational design: Exploring expressive features of imprecision in four digital fabrication approaches. (September 2021) - Zboinska, Malgorzata A; Dumitrescu, Delia
Precision of materialized designs is the conventional goal of digital fabrication in architecture. Recently, however, an alternative concept has emerged which refashions the imprecisions of digital processes into creative opportunities. While the computational design community has embraced this idea, its novelty results in a yet incomplete understanding. Prompted by the challenge of the still missing knowledge, this study explored imprecision in four digital fabrication approaches to establish how it influences the aesthetic attributes of materialized designs. Imprecision occurrences for four different digitally aided materialization processes were characterized. The aesthetic features emerging from these imprecisions were also identified and the possibilities of tampering with them for design exploration purposes were discussed. By considering the aesthetic potentials of deliberate imprecision, the study has sought to challenge the canon of high fidelity in contemporary computational design and to argue for imprecision in computation that shapes a new generation of designs featuring the new aesthetic of computational imperfection.